Asuhan Kebidanan Komprehensif Pada Ny “R” G1P0A0 dengan Ketidaknyamanan Sering Buang Air Kecil Pada Trimester III Menggunakan Pemanfaatan Video Senam Kegel di Klinik A Kabupaten Bandung - Nita Olivia; Damai Yanti (Ide Insan Kreatif, 2023)
Nita Olivia1, Damai Yanti2, Sri Mujiwatii3,Tien Widartini41Prodi D III Kebidanan, STIKes Budi Luhur Cimahi2Prodi D III Kebidanan, STIKes Budi Luhur Cimahi Koresponden: Damai YantiAlamat: Jalan Kerkof No.243, Kota Cimahi; nitaolv@gmail.com ABSTRACT Pregnancy is a process experienced by every woman before giving birth and having children. During pregnancy, labor and the postpartum, there will be some discomfort and complaints, especially in the third trimester. Providing Kegel exercise videos is exercise care through audio-visual media that can be done by pregnant women and postpartum women. The goal is to strengthen the pelvic floor muscles which function to support important organs such as the uterus, bladder and rectum to function properly. Utilization of Kegel exercise videos can increase mothers' attention, imagination, and concentration to do Kegel exercises more often. The method in this study is a case study approach. Collecting data in this study using interviews and observation. The subject of this midwifery care is Mrs. “R” G1P0A0 gestational age 36 weeks 1 day with complaints of frequent urination at the end of gestation. The results of the study during pregnancy showed that dring pregnancy there was an effect of using kegel exercise videos on decreasing that frequency of urination. After the Kegel exercise video was carried out, complaints of frequent urination decreased and the mother felt comfortable. During the postpartum period, mothers were given health education regarding vulva hygiene and video care of Kegel exercises to accelerate perineal wound healing. The conclusion of this case study is the care provided during pregnancy, childbirth, postpartum and newborn to Mrs.